ANALISIS SWOT DALAM PENGEMBANGAN DESA WISATA PULESARI KECAMATAN TURI KABUPATEN SLEMAN - Suwarjo, Warjo (POPULIKA, 2020)
This study aims to conduct a SWOT study in the development of Pulesari Tourism Village, Turi District, Sleman Regency. A qualitative descriptive approach is used to get a complete picture of Pulesari Tourism Village. Primary and secondary research data obtained through interviews, documentation, observation and FGD. The results showed that the development of Pulesari Tourism Village based on SWOT was very much needed. The results of the SWOT study conducted can provide the right strategic direction in the development of the Pulesari Tourism Village. Some of the superior strategies offered: (1) efforts to increase the economic value of zalacca by providing training to process zalacca fruits into various foods and drinks, packaging and marketing them; (2) presenting periodic local traditions as a tourist attraction; (3) increase the number of homestays and increase their eligibility standards as a tourist attraction; (4) Developing distinctive tourism icons that are different from other tourist villages with a choice of distinctive icons "Pulesari Tourism Village: cultural tourism village and outbound river tracking"; and (5) building networks with government agencies and the private sector to get assistance, training and assistance in the procurement and improvement of tourist support facilities as well as improving access to tourist village access roads. Following up on the offer of a number of these strategies, the Pulesari Tourism Village Manager needs to: 1) conduct further studies of the strategies that have been offered through a forum with the tourism village manager to determine the priority scale of the strategy chosen. 2) formulate coordination steps and establish intense communication with various parties, both with the Wonokerto Village Government, Sleman Regency Government through the Department of Tourism, other parties such as companies to obtain budget support as well as training, assistance and facilitation for the development of Pulesari Tourism Village.